Deterministic Competing Failure - Xing, Liudong; Levitin, Gregory; Wang, Chaonan (Dynamic System Reliability, 2019)
Competitions exist in the time domain between the failure isolation effect and the failure propagation effect; different occurrence sequences lead to different system statuses. This chapter discusses a separable method for handling propagated failure with global effects in system reliability analysis. It presents some methods for addressing the competing effects in the reliability analysis of different types of nonrepairable systems, including single‐phase system with single Functional DEPendence (FDEP) group, single‐phase system with multiple dependent FDEP groups, single‐phase system subject to propagated failures (PFs) with global and selective effects, multi‐phase system with single FDEP group, and phased‐mission system with multiple independent or dependent FDEP groups. A PF that originates from a system component causes extensive damages to the rest of the system. The chapter presents a combinatorial reliability analysis method for single‐phase systems subject to competing failures considering both global and selective propagation effects.